2020
DOI: 10.2106/jbjs.20.00203
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes on 90-Day Episodes of Care After Elective Total Joint Arthroplasty Among Medicare Beneficiaries

Abstract: Background: In an effort to improve quality and reduce costs, reimbursement for total knee arthroplasty (TKA) and total hip arthroplasty (THA) in the United States is being based on the value of care provided, with adjustments for some qualifying comorbidities, including diabetes in its most severe form and excluding many diabetes codes. The aims of this study were to examine the effects of diabetes on elective TKA or THA complications and readmission risks among Medicare beneficiaries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…14,41 Interestingly we found that diabetes was a risk factor for readmission following lower extremity arthroplasty, but not upper extremity arthroplasty. This is consistent with other published studies which have shown diabetes as a risk factor for readmission following total hip and knee arthroplasty 42 but not following total elbow or shoulder arthroplasty. 43,44 The exact reasoning for this finding is unclear and further studies are needed to better define the role of diabetes, perioperative glucose control, and target thresholds for hemoglobin A1c on readmission after joint arthroplasty.…”
Section: Discussionsupporting
confidence: 93%
“…14,41 Interestingly we found that diabetes was a risk factor for readmission following lower extremity arthroplasty, but not upper extremity arthroplasty. This is consistent with other published studies which have shown diabetes as a risk factor for readmission following total hip and knee arthroplasty 42 but not following total elbow or shoulder arthroplasty. 43,44 The exact reasoning for this finding is unclear and further studies are needed to better define the role of diabetes, perioperative glucose control, and target thresholds for hemoglobin A1c on readmission after joint arthroplasty.…”
Section: Discussionsupporting
confidence: 93%
“…However, controlled-complicated diabetes had the largest odds for TJR readmissions and complications, and the risks for TJR readmissions were comparable to uncontrolled diabetes. [33] In our study, patients with diabetes were associated with higher rates of readmission following TJR, which reflected prior authors' conclusions.…”
Section: Discussionsupporting
confidence: 89%
“…The HRs were comparable to those seen with comorbidities commonly screened for and managed, such as diabetes mellitus and cardiovascular disease. 37,38 Thus, the identification and management of depression and anxiety preoperatively may represent a major untapped and underappreciated opportunity for orthopaedic surgeons to improve both the surgical outcomes and the overall health of up to one-third of their patients.…”
Section: Discussionmentioning
confidence: 99%